RNA-Seq analysis of laser-capture microdissected cells of the developing central starchy endosperm of maize - Thakare, Dhiraj; Yang, Ruolin; Steffen, Joshua G.; Zhan, Junpeng; Wang, Dongfang; Clark, Richard M.; Wang, Xiangfeng; Yadegari, Ramin (Genomics data, 2014)
Endosperm is a product of double fertilization, and provides nutrients and signals to the embryo during seed development in flowering plants. Early stages of endosperm development are critical for the development of its storage capacity through synthesis and accumulation of starch and storage proteins. Here we report on the isolation and sequencing of mRNAs from the central portion of the starchy endosperm of Zea mays (maize) B73 at 6days after pollination. We detected a high level of correlation among the four biological replicates of RNAs isolated using laser-capture microdissection of the cell type. Because the assayed developmental stage precedes the synthesis and accumulation of the major storage proteins and starch in the endosperm, our dataset likely include mRNAs for genes that are involved in control and establishment of these storage programs. The mRNA-Seq data has been deposited in Gene Expression Omnibus (accession number GSE58504).